Heat transfer enhancement in flow past triangular turbulence promoters in closed channels - Gargioni G.T. (2019)
© 2019, © 2019 Taylor & Francis Group, LLC.The global competitiveness has led industries to investigate innovative strategies to increase heat transfer. This work is inserted within this context and focuses on heat transfer enhancement in plane channels using triangular turbulence promoters. The SST turbulence model is adopted owing to its improved capacity to simulate flows with adverse pressure gradients. Verification and validation are performed by comparing numerical results against theoretical/experimental/numerical data for a plane channel and backward facing step. The location of the turbulence promoters was investigated and the best performance (minimum pressure drop/maximum heat transfer rate) was achieved when the turbulence promoters are aligned and positioned close to one of the channel walls.